Cochrane Schizophrenia Group's Study-Based Register of Randomized Controlled Trials: Development and Content Analysis. Issue 1 (27th November 2020) - Shokraneh, Farhad; Adams, Clive E
Abstract: Background: Study-based registers facilitate systematic reviews through shortening the process for review team and reducing considerable waste during the review process. Such a register also provides new insights about trends of trials in a sub-specialty. This paper reports development and content analysis of Cochrane Schizophrenia Group's Study-Based Register. Methods: The randomized controlled trials were collected through systematic searches of major information sources. Data points were extracted, curated and classified in the register. We report trends using regression analyses in Microsoft Excel and we used GIS mapping (GunnMap 2) to visualize the geographical distribution of the origin of schizophrenia trials. Results: Although only 17% of trials were registered, the number of reports form registered trials is steadily increasing and registered trials produce more reports. Clinical trial registers are main source of trial reports followed by sub-specialty journals. Schizophrenia trials have been published in 23 languages from 90 countries while 105 nations do not have any reported schizophrenia trials. Only 9.7% of trials were included in at least one Cochrane review. Pharmacotherapy is the main target of trials while trials targeting psychotherapy are increasing in a continuous rate. The number of people randomized in trials is on average 114 with 60 being the most frequent sample size. Conclusions: Curated datasets within the register uncover new patterns in data that have implications for research, policy, and practice for testing new interventions in trials or systematic reviews.